Rosyjskie homografy czasownikowe - Kaliszan, Jerzy (Studia Rossica Posnaniensia, 2010)
The article is devoted to the study of Russian verbal homographs such as икать – икать, насыпать – насыпать, белите – белите. The author thoroughly investigates all kinds of verbal homographic oppositions existing in contemporary Russian.